1998
DOI: 10.1093/ajcn/68.6.1272
|View full text |Cite
|
Sign up to set email alerts
|

The nondigestible fat sucrose polyester does not stimulate gallbladder emptying in humans

Abstract: Ingestion of sucrose polyester, in contrast with digestible fat, did not stimulate gallbladder emptying or release of cholecystokinin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Another explanation for the increased excretion with olestra is that olestra in the intestinal lumen increased transport of hexachlorobenzene into the lumen. Because olestra probably does not stimulate bile flow (13,16), this process would require direct secretion from the enterocyte in a nonbiliary excretion (11,24). It is indeed possible that the sequestration of hexachlorobenzene in the intestinal lumen increased the concentration gradient from the enterocyte to the lumen and thereby enhanced transport.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the increased excretion with olestra is that olestra in the intestinal lumen increased transport of hexachlorobenzene into the lumen. Because olestra probably does not stimulate bile flow (13,16), this process would require direct secretion from the enterocyte in a nonbiliary excretion (11,24). It is indeed possible that the sequestration of hexachlorobenzene in the intestinal lumen increased the concentration gradient from the enterocyte to the lumen and thereby enhanced transport.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that various diseases and habits affect the gallbladder via different mechanisms, predisposing it to stones. For example, gallbladder may be predisposed to stones in cholecystokinin deficiency in patients receiving long term parenteral nutrition treatment [ 1 ], as well as autonomic nervous system dysfunctions in such connective tissue diseases as rheumatoid arthritis and systemic lupus erythematosus [ 4 ] and reduced post-prandial gallbladder volume in case of low physical activity and chronic smoking [ 21 , 22 ]. Irrespective of the primary cause, the main problem in all these examples is the biliary stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Gallbladder contraction induced by cholecystokinin secretion is followed by the emptying of the stored bile. Impairment or failure of this mechanism causes gallbladder hypomotility [ 1 , 2 ]. In addition to many risk factors which primarily cause increased cholesterol saturation in bile such as genetic factors, obesity, sudden weight loss, hyperlipidemia and high calorie diet, gallbladder hypomotility, followed by delayed gallbladder emptying and biliary stasis, plays a significant role in gallstone formation [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%